Dampak Project-Based Learning terhadap Keterampilan Kolaborasi Siswa - Muinah, Muinah; Ningrum, Fhela Vhantoria; Rasmawati , Yesa Dwi (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
This study was motivated by the low collaboration skills of students, which were reflected in the lack of active participation in discussions, lack of responsibility in group assignments, and the tendency to discuss outside the learning topic. This study aims to analyze the impact of the implementation of the Project-Based Learning (PjBL) model on the collaboration skills of class VII students at SMP Negeri 7 Kotabumi. The study used a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of class VIIA as the experimental group and VIID as the control group, each with 35 students. Data were collected through questionnaires and authentic assessment observations. Data analysis was carried out using parametric statistical tests. The results of the study indicate that the Project-Based Learning (PjBL) model has a significant impact on students' collaboration skills. Hypothesis testing at a significance level of 0.05 produces a tcount value = 2.31> ttable = 1.995, so the null hypothesis is rejected. This indicates that the implementation of Project-Based Learning (PjBL) has a positive impact on collaboration skills. Conclusion, the Project-Based Learning (PjBL) model has a positive impact on students' collaboration skills and can be an alternative innovative learning to face the challenges of 21st century education.